Answer:
f'''(x)=-5(x-1)^2
Explanation:
Given:
f(x)= x^2
Shifting 1 unit to right means subtracting 1 from the function i.e
f(x-1)=(x-1)^2
f'(x)=(x-1)^2
now vertically stretching above f'(x) by a factor of 5:
5f'(x)=5(x-1)^2
f''(x)=5(x-1)^2
finally reflecting above f'''(x) over the x-axis:
-f''(x)=-5(x-1)^2
f'''(x)=-5(x-1)^2 !
The given parent function is:
If we shift to the right by 1 unit, the function becomes:
If we stretch by a factor of 5, the function becomes,
Finally reflecting over the x-axis gives:
5.3m questions
6.8m answers